The Role of Bahtsul Masail in Improving the Understanding of Jurisprudence of Santri at Manbaul Hikam Islamic Boarding School in Burneh Bangkalan - Ahmad Musadad; Baihaqi, Baihaqi; Muttaqin Choiri; Tri Pujiati; Asmoi, Asmoi (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2025)
Discussion forums organized in Islamic boarding schools (pesantren) are one of the most effective means to support students’ understanding of scientific material in the yellow classical books (kitab kuning). Bahtsul masail is a typical religious discussion forum in the pesantren tradition, which is used to examine contemporary issues through a fiqih perspective. This research explores the role of bahtsul masail in improving the understanding of fikih among the santri of Pondok Pesantren Manbaul Hikam Burneh, Bangkalan. This study uses a qualitative approach with a descriptive method, involving observation, in-depth interviews, and documentation analysis as data collection techniques. The results show that bahtsul masail plays a significant role in deepening the fikih understanding of santri, especially in terms of the practical application of Islamic law. The intensive and collaborative discussions in bahtsul masail encourage santri to think critically and analytically on complex issues, which in turn strengthens their intellectual and religious skills. This study concludes that Bahtsul Masail is an important instrument in pesantren education that is effective in producing knowledgeable and insightful santri. This study gives implication that bahtsul masail as the main learning method that not only encourages the improvement of santri's knowledge in religious sciences, but also develops their skills in scientific and religious argumentation through interactive and collaborative discussions.